FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN PASIEN DIARE PADA ANAK DI RSUD MAJENANG KABUPATEN CILACAP TAHUN 2008 - -, Karyono; -, Basirun; Septiwi, Cahyu (Jurnal Ilmiah Kesehatan Keperawatan, 2009)
This research aim to know the factors influencing diarrhea occurrence in RSUD Majenang year 2008 and to know the most dominant factor of  its influence to diarrhea occurrence. This Research type is observational research by design of research is cross sectional approach. Population in this research is family member who suffered from diarrhea at Majeneng General Hospital. Sample was taken by purposive sampling method. The number of respondents was 83. Statistical analysis used is Multiple Regression Logistics to know the dominant factor from a number of variable independent that is infection, personal hygiene and environmental sanities to diarrhea occurrence. Result of research shown that there are significance relation between infection factor to diarrhea occurrence. Pursuant to analyze result of logistics regression known that the value significance ( sig.) for the variable of infection  equal to 0,005 smaller than a ( 0,05). There are significance relation between factor of personal hygiene with the diarrhea occurrence. Pursuant to result analyses of logistics regression known that the significance value ( sig.) for the variable of personal hygiene equal to 0,043 smaller than a  ( 0,05). There are significance relation between environmental sanities factor with diarrhea occurrence. Result of analysis of logistics regression obtained that significance value ( sig.) for the variable of environmental sanitize equal to 0,021 smaller than a ( 0,05). And pursuant to result analyzes the logistics regression known that the highest wald value is infection variable that is equal to 7,850 with the significance value ( sig.) equal to 0,005 smaller thana ( 0,05) so that most dominant factor its influence to diarrhea occurrence infection factor. The Research conclusion is that there are significant relation between infection factor, personal Hygiene and environmental sanitize with the diarrhea occurrence of most dominant factor and its influence to diarrhea occurrence is infection factor   Keywords: infection, personal hygiene, environmental sanities, diarrhea disease